Perifoveal S-cone and rod-driven temporal contrast sensitivities at different retinal illuminances - Huchzermeyer, Cord; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2017)
We evaluated a technique for measuring temporal contrast sensitivities to sine-wave modulation driven by S-cones and rods in the perifovea using triple silent substitution. Isolating stimuli for S-cones and rods were created using an eight-channel, four-primary LED stimulator that has been validated before. Sensitivities were measured at 10 different temporal frequencies between 1 and 28 Hz in three normal observers at 14 different retinal illuminances between 0.07 and 587 photopic troland (phot Td) and at three different retinal illuminances over the same range in one S-cone monochromat. The technique was further validated by measuring bleaching adaptation in two normal subjects, demonstrating sufficient isolation in rods. Good isolation was apparent from the differences in the temporal contrast sensitivity functions and the sensitivity-versus-retinal illuminance functions between S-cones and rods, and also from the results in the S-cone monochromats and the delayed recovery of rod sensitivities after bleaching. The results will help to determine optimal stimulus conditions in future studies. The results in the S-cone monochromat demonstrate the potential clinical value of our protocol.
EVALuna2:21334